2011
DOI: 10.1007/s00421-011-2276-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of urine toxic metals concentrations in athletes and in sedentary subjects living in the same area of Extremadura (Spain)

Abstract: Cadmium (Cd), tungsten (W), tellurium (Te), beryllium (Be), and lead (Pb), are non-essential metals pervasive in the human environment. Studies on athletes during training periods compared to non-training control subjects, indicate increased loss of minerals through sweat and urine. The aim of this study was to compare the level of these trace elements, determined by inductively coupled plasma mass spectrometry (ICP-MS) in urine samples, between athletes and age-matched sedentary subjects living in the same ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 26 publications
1
10
0
1
Order By: Relevance
“…Previous studies in subjects exposed to Pb, reported decreases in blood Pb after aerobic training [32]. In urine, similar results were obtained previously [17]. This could indicate, as in the case of Cd, a natural strategy (physical activity) to reduce the Pb levels in the body, especially in industrialized areas or big cities, due to the high amounts of this mineral in the air.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Previous studies in subjects exposed to Pb, reported decreases in blood Pb after aerobic training [32]. In urine, similar results were obtained previously [17]. This could indicate, as in the case of Cd, a natural strategy (physical activity) to reduce the Pb levels in the body, especially in industrialized areas or big cities, due to the high amounts of this mineral in the air.…”
Section: Discussionsupporting
confidence: 84%
“…Furthermore, previous studies found a significant increase in Cd excretion after an exercise until exhaustion [19], and a higher urinary concentration in athletes with respect to the control group [17]. In this respect, major excretion could be expected after 6 months of physical training, but no time effect was observed.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Recent data have shown that exposure to Cd leads to an increase in plasma levels of adrenocorticotropic hormone (ACTH) [60], a hormone secreted by the pituitary gland that controls the release of C in the adrenal gland [61]. Pérez-Cadahía et al [62] reported positive relationships between C and Cd, that indicate that this mineral could have an implication with the catabolic processes that occur in the body, so the runner's body attempts to eliminate Cd although its concentrations are normal in order to avoid this negative effect [63]. Future studies are required to clarify this point.…”
Section: Discussionmentioning
confidence: 99%
“…Urinary tungsten in 21 athletes was reported to be 82 ± 53 μg/g-creatinine whereas levels in 26 sedentary subjects were below the limit of detection ( Llerena et al 2012 ). Another investigation examined the possible relationship between metals in children and severity of autism.…”
Section: Toxicological Studiesmentioning
confidence: 99%